Deskripsi Proses Pemberian Ganjaran dan Hukuman oleh Instruktur Kepada Peserta Didik di Lembaga Kursus English Tutorial Centre Padang - Lasmi Maharani; Setiawati Setiawati (Universitas Negeri Padang, 2018)
This research is motivated by the high participation of learners English in the course of English Tutorial Center Padang, visible high level of attendance, liveliness and discipline of learners. Researchers suspect that the cause of the high participation of learners is due to the process of reward and punishment by the instructor in the learning activities. This study aims to describe the process of reward and punishment by instructors in English learning activities. This type of research is quantitative descriptive research. The population in this study were all students totaling 500 people. Sampling technique used is cluster sampling, samples taken at each level/study group as many as 50 people. Data collection techniques using questionnaires. While the data collection tool use a list of statements. Data analysis techniques use a percentage formula. The results show that rewards in of point, reward, and praise are categorized both given by the instructor, as well as punishments in prefentive and repressive forms categorized well given by the instructor. This is evidenced by the majority of students expressing